A Critique on the Legal Framework for ‘Guardian Ad Litem’ in India with Specific Reference to the Principle of Participation in Child Custody Disputes - Saksena, Sugandh (Christ University Law Journal, 2025)
This paper seeks to highlight the significance of Guardians Ad Litem (GAL) with respect to participation of children in judicial proceedings. While GAL in various other jurisdictions is vested with diverse roles and well stipulated qualifications; the Indian model reflects a more limited role and an inherently paternalistic approach towards a child’s participation in judicial proceedings involving his/her interest. Deeply imbibed in the welfare principle, the provisions for a child’s representation through GAL in the legal framework seems inadequate due to the immense importance given to natural guardians and the lack of specialized qualifications in the statutory provisions. The paper further seeks to highlight, that despite of the statutory recognition of a child’s right to legal aid and representation under the Juvenile Justice (Care and Protection of Children) Act 2015 and the Protection of Children from Sexual Offences Act, 2012; the role of a GAL which vests primarily with the guardians of the children might result counter operative when such a guardian itself is guilty of abuse or neglect. Moreover, a near absence of any such provision in the child custody dispute within the legal framework, may seriously impair the right of a child considering the immense trauma a child might have to undergo in a custody battle.